God as a private matter: Culture of memory and religious life in socialism - Lidija Radulović (Etnoantropološki Problemi, 2014)
The revitalization of religion in postsocialism is followed by the revitalization of individual narratives about religious life in socialism. On the one hand, the lived experience is connected to the contemporary revitalization of religion and the public discourse promoted by the Serbian Orthodox church on the repression it suffered during socialism, and on the other hand, interlocutors tell of their positive experiences which stand in contrast to official stories. The research presented in this paper is directed toward the conceptualization of individual narratives which actualize the memories of the faithful of the life during socialism. Special attention has been paid to those aspects of the past which interlocutors consider relevant for interpreting their own relationship with religion, meanings attributed to memories and ways in which they are connected and interpreted i the context of the present.